Der Wirkungsgrad von Training - Böning D; Maassen N; Steinach M (Deutsche Zeitschrift für Sportmedizin)
The efficiency of energy conversion is defined astheratio between muscular power and metabolic energy expenditure. Following definitions are used: gross(muscular power/total energy expenditure), net (muscular power/(total energy expenditureresting energy expenditure)), work (muscular power/(total energy expenditureidling energy expenditure)), delta (muscular power/energy expenditure). net of isolated muscles amounts to 30%. Because of supporting functions, lower values result in vivo during positive exercise. During negative exercise the body often storesenergy (elastic, potential, kinetic) which markedly improves if reused. Measurements are performed using ergometers (cycle ergometers, treadmill etc.) and indirect calorimetry (VO2 and VCO2). Determination of both gases is essential, because varying proportions of fat and carbohydrate oxidation influence energy turnover. For intense exercise,the anaerobic energy yield is calculated from oxygen deficit or blood lactate. Measurements have to be standardized, because movement frequency and power influence . For comparisons net, which little depends on power is preferable. During sports, values vary between 1% (arching) and 50%(running). Measurement of energy expenditure per m distance and kg of body mass is also applicable for efficiency estimation. The efficiency of complex movements can be improved by practicing,sinceoptimized coordination reduces energy need. Aging and fatigue are therefore also influential. The mitochondrial function is probably not trainable. Clear sex differences have not been observed. An improvement of efficiency in hypoxia is improbable; a relative increase of carbohydrate metabolism reduces the need for oxygen. An increase of efficiency by nitrate consumption is under discussion.KEY WORDS: Energy Expenditure, Ergometry, Respiratory Quotient, Physical Training, Altitude, Nitrogen Monoxide